IMPLEMENTASI APLIKASI NASKAH DINAS ELEKTRONIK (E-OFFICE) DI BIRO PEMERINTAHAN SEKRETARIAT DAERAH PEMERINTAH PROVINSI DAERAH KHUSUS JAKARTA - Amirah Amirudin, Dinda; Nurcahyanto, Herbasuki (Journal of Public Policy and Management Review, 2025)
Implementation of Electronic Official Script Application (e-Office) by Government Bureau of the Regional Secretariat of the Provincial Government of the Jakarta Special Region aims to improve the management and governance indexes in the application of e-Government. However, various issues have been identified in its implementation, such as manual disposition, incomplete archiving features, technical disruptions, risky practices of sharing usernames and passwords, and low employee commitment. This study aims to analyze the implementation of e-Office in the Government Bureau of the Regional Secretariat of the Provincial Government of the Jakarta Special Region and identify the factors that support and hinder its implementation. Data were collected through interviews, observations, documentation, and literature studies, referring to the seven principles of SPBE, namely effectiveness, integration, sustainability, efficiency, accountability, interoperability, and security, as well as the supporting and hindering factors of policy implementation according to Edward III, which are communication, resources, disposition, and bureaucratic structure. The results of the study show that the implementation of e-Office has improved effectiveness, efficiency, accountability, and integration in administrative management, although challenges remain in the aspects of sustainability, interoperability, and security. Communication, disposition, and bureaucratic structure are supportive factors, while limited human resource competencies constitute the main obstacle. Recommendations include strengthening a centralized backup data storage system, integrating e-Office with other applications, improving security through two-factor authentication, data encryption, and access restrictions, implementing an e-Office mentoring program, and automating workflows to simplify the approval process.